2018
DOI: 10.1590/0366-69132018643692215
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of Cr-beidellite treated up to 1350 °C in oxygen or nitrogen atmospheres

Abstract: Beidellite clay mineral after intercalation of OH-Cr(III) species were thermally analyzed up to 1350 °C in oxygen and nitrogen atmospheres. OH-Cr-beidellite can be used as a pillared clay precursor for catalysis or as adsorbent applications. However, in this paper beidellite enriched in chromium were analyzed at different thermal treatments up to high temperature for evaluating structural changes for possible future ceramic applications. The structural changes were followed by thermal analysis and X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Akpomie and Dawodu (2016) [ 67 ] reported changes in the peaks of montmorillonite treated with acid medium, indicating an alteration in the alumina content. Similarly, effects were observed in beidellite intercalated with chromium [ 63 ] and in clinoptilolite intercalated with cadmium [ 68 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Akpomie and Dawodu (2016) [ 67 ] reported changes in the peaks of montmorillonite treated with acid medium, indicating an alteration in the alumina content. Similarly, effects were observed in beidellite intercalated with chromium [ 63 ] and in clinoptilolite intercalated with cadmium [ 68 ].…”
Section: Discussionmentioning
confidence: 87%
“…Another component of smectites is beidellite [ 62 ]; this mineral was observed in both C-2 clay (55.0%) and C-3 clay (36.5%), with the corresponding XRD peaks. Santos et al (2018) [ 63 ] observed reflexions of beidellite at 2θ = 7.1 and 14.2°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation